The Development of Teaching Materials Based Outcome-Based Education Curriculum to Encourage Teacher Skill - Setiawan Edi Wibowo; Sujarwo Sujarwo (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2022)
This study seeks to describe the development of teaching materials in the Elementary Indonesian Language and Literature Learning Development Course in the Elementary School Teacher Education Study Program, Yogyakarta State University. This research is included in qualitative research. The setting of this research is in the Elementary School Teacher Education Study Program, Yogyakarta State University on 27 September 2021 to 27 September 2021. The data of this research are in the form of issues that arise in the Elementary School Teacher Education Study Program, Faculty of Education, Yogyakarta State University. Sources of data in this study were students, lecturers, and stakeholders of the Faculty of Education, State University of Yogyakarta. Data collection techniques using interviews and documentation. Data analysis techniques in this study used qualitative data analysis techniques. The result of this research is the idea to solve this problem is to develop syllabi and teaching materials for the Indonesian Language and Literature Learning Development Course, which is oriented towards the OBE curriculum. In the implementation of this stuttering, there is a change in the arrangement of stages, namely prioritizing stage IV, namely compiling teaching materials for the SD Indonesian Language and Literature Learning Development Course concerning the OBE Curriculum.